Exploring the mechanism by which tourists’ perceived value influences revisit intention in sustainable gardens: A case study of KICG-sustainable garden, Shanghai - JiaJun Chen; Guanxi Chen (PLoS ONE, 2026)
Sustainable gardens have emerged as innovative models of urban tourism that integrate ecological aesthetics, participatory design, and community well-being. This study explores how tourists’ perceived value influences revisit intention and introduces two experiential moderators—narrative transportation and empowerment capability—to uncover the underlying psychological and participatory mechanisms that drive behavioral intention. A mixed-methods approach was employed, combining grounded theory interviews to develop the conceptual framework with a large-scale survey analyzed using structural equation modeling (SmartPLS). The results demonstrate that perceived value positively affects revisit intention through tourist satisfaction, while narrative transportation and empowerment capability significantly strengthen these relationships by enhancing emotional immersion and participatory engagement. These findings advance sustainable tourism theory by highlighting the dual-path moderating effects of storytelling and empowerment in shaping visitor behavior. Practically, the study provides actionable insights for sustainable garden management, emphasizing the importance of immersive narratives and participatory empowerment in fostering long-term tourist loyalty and sustainable destination development.